The relationship of explosive force and some biomechanical variables to the accuracy of the volleyball smash performance (Global Scientific Review, 2024)
When building a movement on solid foundations that the player understands, it is necessary to seek help from the science of biomechanics. This science has the highest degree of connection with the rest of the other sciences, most notably the science of sports training, as the causes of movement and its weaknesses and strengths are traced back to the mechanism. Likewise, the role of modern technologies in measuring and monitoring the development accompanying all operations is not hidden. Development, and through this, the importance of research appears in knowing the relationship between the explosive power of the arms and legs and performing the skill of crushing the volleyball. As for the problem of the research, and through the researchers’ observation, In school tournaments and some school tournaments, there is a weakness in the skill performance of the volleyball smashing skill. This weakness may be due to a lack of attention to the explosive power on which the smashing skill and some biomechanical variables depend